MATERIAL REGENERATION AND CULTURAL SUSTAINABILITY THROUGH MODULAR FASHION DESIGN: RECONCEPTUALIZING BALINESE ENDEK WEAVING SCRAPS - Ni Kadek Yuni Diantari; Gede Bayu Segara Putra; Anak Agung Gede Rai Remawa; I Wayan Dedy Prayatna; I Putu Udiyana Wasista (Institut Seni Indonesia Bali, 2026)
The fashion industry generates textile waste throughout the production and consumption stages, while leftover Balinese endek weaving fabric is still frequently treated as production residue that remains underutilized. This study aims to develop a sustainable modular fashion design model based on leftover Balinese endek fabric by integrating the principles of less waste design, subtraction pattern, draping, Traditional Ecological Knowledge (TEK), and regenerative design. The research employed a qualitative approach using a Research Through Design strategy, involving participant observation of the design process, visual documentation, in-depth interviews with designers and artisans, analysis of pattern and prototype documentation, as well as thematic and design analysis. The findings reveal that leftover endek fabric can be classified according to size, motif, texture, grain direction, and joining potential to form structural panels, visual elements, and transitional modules. Subtraction pattern and draping enable irregular fabric remnants to be negotiated with the body, while the modular system expands possibilities for configuration, functionality, and product life cycles. These findings demonstrate that leftover endek fabric should not be viewed merely as textile waste but as a cultural material that embodies ecological, technical, and symbolic values. This article contributes to the sustainable fashion discourse by proposing the concept of tradition subtraction as a design approach that connects material efficiency, the regeneration of local textile values, and the development of a tradition-based circular economy.